Anti-inflammatory salicylate treatment alters the metabolic adaptations to lactation in dairy cattle - Farney, Jaymelynn K.; Mamedova, Laman K.; Coetzee, Johann F.; KuKanich, Butch; Sordillo, Lorraine M.; Stoakes, Sara K.; Minton, J. Ernest; Hollis, Larry C.; Bradford, Barry J. (My University, 2013)
Adapting to the lactating state requires metabolic adjustments in multiple tissues, especially in the dairy cow, which must meet glucose demands that can exceed 5 kg/day in the face of negligible gastrointestinal glucose absorption. These challenges are met through the process of homeorhesis, the alteration of metabolic setpoints to adapt to a shift in physiological state. To investigate the role of inflammation-associated pathways in these homeorhetic adaptations, we treated cows with the nonsteroidal anti-inflammatory drug sodium salicylate (SS) for the first 7 days of lactation. Administration of SS decreased liver TNF-α mRNA and marginally decreased plasma TNF-α concentration, but plasma eicosanoids and liver NF-κB activity were unaltered during treatment. Despite the mild impact on these inflammatory markers, SS clearly altered metabolic function. Plasma glucose concentration was decreased by SS, but this was not explained by a shift in hepatic gluconeogenic gene expression or by altered milk lactose secretion. Insulin concentrations decreased in SS-treated cows on day 7 compared with controls, which was consistent with the decline in plasma glucose concentration. The revised quantitative insulin sensitivity check index (RQUICKI) was then used to assess whether altered insulin sensitivity may have influenced glucose utilization rate with SS. The RQUICKI estimate of insulin sensitivity was significantly elevated by SS on day 7, coincident with the decline in plasma glucose concentration. Salicylate prevented postpartum insulin resistance, likely causing excessive glucose utilization in peripheral tissues and hypoglycemia. These results represent the first evidence that inflammation-associated pathways are involved in homeorhetic adaptations to lactation.the transition from late pregnancy to lactation is a time of great physiological stress, especially for the dairy cow. The decline in feed intake that accompanies parturition, coupled with the rapid increase in energy requirements during lactogenesis, requires a dramatic shift in nutrient fluxes to release stored nutrients and direct them to the mammary gland. This programmed shift in metabolic setpoints is an archetypal example of homeorhesis, defined as the “coordinated changes in metabolism of body tissues necessary to support a physiological state” (4).Mechanisms underlying homeorhetic adaptions to lactation have been described to some extent. The somatotropic axis is decoupled during this time, resulting in dramatic elevations of plasma growth hormone concentrations without the expected rise in insulin-like growth factor 1 secretion (11, 51). Likewise, insulin sensitivity declines substantially from late gestation (5, 48). These endocrine shifts are critical for promoting the mobilization of stored nutrients and sparing glucose for use by the mammary gland. This conservation of glucose is particularly important in ruminants. The microbes that inhabit the rumen ferment most dietary carbohydrate to volatile fatty acids, leaving very little glucose to be absorbed in the small intestine. As a result, lactating cows absorb almost no glucose from the gastrointestinal tract and must synthesize as much as 5 kg of glucose in the liver daily (2).The homeorhetic adaptations that allow cows to increase milk production to 40 kg/day within days after parturition can stress the metabolic system. Rapid lipolysis can increase plasma nonesterified fatty acid (NEFA) concentrations by as much as 10-fold within a few days after parturition (21), and both hypoglycemia and hypocalcemia are common, as nutrients are drawn into the mammary gland. Ketosis and fatty liver (FL) are common metabolic diseases that result during this time; in fact, nearly 90% of all metabolic diseases in dairy cattle occur during the first 4 wk of the 305-day lactation (24).Despite their reliance on mobilized lipid as an energy source, dairy cattle entering lactation with greater adipose mass are at greater risk of developing metabolic diseases (34). It has become clear in the past decade that animals with excessive adiposity exhibit a low-grade inflammation (23), suggesting that perhaps inflammation underlies metabolic disturbances in obese dairy cows. In support of this hypothesis, cows with moderate or severe FL have increased levels of the inflammatory cytokine TNF-α (41). Inflammatory cytokines cause myriad metabolic changes in dairy cattle, including anorexia, lipomobilization, impaired insulin sensitivity, and reduced milk yield (7, 26, 27), all of which are associated with FL and ketosis. Furthermore, daily injection of TNF-α for 7 days increased liver triglyceride content independent of effects on feed intake, and this effect was accompanied by changes in hepatic gene expression consistent with both inflammation and a shift from fatty acid oxidation to triglyceride synthesis (8).These recent findings suggest that exogenous inflammatory agents are sufficient to induce metabolic dysfunction. Whether inflammation is a necessary causative factor in the natural progression of bovine FL and ketosis, however, remains unclear. To address this broad question, we used the nonsteroidal anti-inflammatory drug (NSAID) sodium salicylate (SS). Sodium salicylate is a weak inhibitor of cyclooxygenase (COX)-1 and COX-2 (31), and its probable mode of action is that it inhibits phosphorylation of the NF-κB inhibitor IκB-α (53). Phosphorylation of IκB results in its degradation, allowing NF-κB to be released for translocation into the nucleus and subsequent activation of an inflammatory transcription program (3). The specific hypothesis for this study was that SS would slow liver triglyceride accumulation, promote gluconeogenesis, and limit metabolic disease in dairy cows entering lactation. In contrast, our findings suggest that inflammatory signals may contribute to homeorhetic adaptations to lactation, especially regulation of glucose metabolism and modulation of lipolysis and ketogenesis as animals return to positive energy balance.
Citation:Farney, J. K., Mamedova, L. K., Coetzee, J. F., KuKanich, B., Sordillo, L. M., Stoakes, S. K., … Bradford, B. J. (2013). Anti-inflammatory salicylate treatment alters the metabolic adaptations to lactation in dairy cattle. American Journal of Physiology-Regulatory, Integrative and Comparative Physiology, 305(2), R110–R117. https://doi.org/10.1152/ajpregu.00152.2013
Keywords: homeorhesis; salicylate; metabolism